Peranserta Ibu Rumah Tangga dalam Community Self Survey Mempengaruhi Frekuensi Pemberantasan Sarang Nyamuk dan Container Index di Pakuncen Kota Yogyakarta - Sri Handayani; Lucky Herawati; Achmad Husein (Poltekkes Kemenkes Yogyakarta, 2015)
Pakuncen is one of the villages in Wirobrajan of Yogyakarta City with larva-free index below the national target, i.e. 87 %. This reflects high container index (CI) and lack of the awareness among housewives in conducting mosquito nest eradication. The research was aimed to know the effect of housewives participation in community self-survey to the frequency of the eradication and container index in that village by conducting a quasi experiment with non equivalent control group design. Subjects of the research were 52 housewives live in RT 28 and RT 29, of RW 6 in Kleben Hamlet, Pakuncen Village, who were then divided into two group, the experiment group and the control group. At the beginning of the study, all the housewives were provided with conseling. Later, treatment in the form of participation in community self survey was implemented in the experiment group, meanwhile in the control group it was not. The instruments used were questionnaire and larvae observation sheet. Data were analyzed with non parametric Kruskal-Wallis test at 0,05 level of significance, and the results showed that housewives participation in the community self-survey influenced the frequency of eradication activeties (p-value = 0,018). Nonetheless, the study could not prove statistically that the participation had significant effect to CI (p-value = 0,400) even though in the experiment group a decrease of CI was observed.